تغير المقاومة النوعية للكاوتشوك (نايريت) المشوب بنسب مختلفة من الغرافيت بتابعية تغير درجة الحرارة (Latakia University Journal -Basic Sciences Series, 2018)
من خلال دراسة المركبات الناتجة من إضافة الغرافيت إلى الكاوتشوك وفق النسب:    ,    ,    ,    تبيّن لنا أن زيادة نسبة الغرافيت تؤدي إلى تغير في المقاومة النوعية من جهة، ومن جهة أخرى فإن تأثير درجة الحرارة على خواص هذه المركبات لا يكون بشكل متماثل وإنما يتبع نسبة الغرافيت المضافة. فمن أجل الكاوتشوك النقي تكون الزيادة في قيمة المقاومة النوعية ليست كبيرة ولا تتعدى القيمة    عند تناقص درجة الحرارة. أما من أجل النسب الأخرى فان المقاومة النوعية تتغير ضمن مجال (  -   )، بالإضافة إلى كون التغير يأخذ شكلاً متناقصا، اعتباراً من النسبة    وما فوق. كما تم تعيين قيم تغير طاقة التنشيط لهذه المركبات بزيادة نسبة الغرافيت المدخلة إليها، بالإضافة إلى تفسير سلوك المقاومة النوعية للعينات الحاصلة بتغير درجة الحرارة.   أجريت القياسات في جامعة يريفان الحكومية (جمهورية أرمينيا) – 2005 م. A study of the compounds resulting from additional of graphite to rubben in accordance with the following rates:  1:0.05 – 1:0.15 – 1:0.25 – and 1:0.75, shows that if the increase of graphite ratio leads to change of the resistivity. Then, the influence of temperature on the properties of these compounds will not be similar but will follow the ratio of added graphite. As for the pure rubber we shall not encounter a great increase in the value of resistance till the values located within the range 10  when temperature decreases. With regards to the other ratios the resistance will change within the range of  (  -  ( Maximum. Besides the alteration takes an opposite shape standing from ratio 1:0,15 upwards. Moreover, determination was done for the values of activation energy change of these compounds when increasing the quality of graphite added to them, in addition to explanation of the behavior of resistance available when changing the temperature.   Tests were performed in Yerivan state university (republic of Arminia) in  2005.